Human-centric interfaces for ambient intelligence - Aghajan, Hamid K. (Academic, 2009)
To create truly effective human-centric ambient intelligence systems both engineering and computing methods are needed. This is the first book to bridge data processing and intelligent reasoning methods for the creation of human-centered ambient intelligence systems. Interdisciplinary in nature, the book covers topics such as multi-modal interfaces, human-computer interaction, smart environments and pervasive computing, addressing principles, paradigms, methods and applications. This book will be an ideal reference for university researchers, R & D engineers, computer engineers, and graduate students working in signal, speech and video processing, multi-modal interfaces, human-computer interaction and applications of ambient intelligence. Hamid Aghajan is a Professor of Electrical Engineering (consulting) at Stanford University, USA.-His research is on user-centric vision applications in smart homes, assisted living / well being, smart meetings, and avatar-based social interactions. He is Editor-in-Chief of "Journal of Ambient Intelligence and Smart Environments", has chaired ACM/IEEE ICDSC 2008, and organized workshops/sessions/tutorials at ECCV, ACM MM, FG, ECAI, ICASSP, CVPR. Juan Carlos Augusto is a Lecturer at the University of Ulster, UK. He is conducting research on Smart Homes and Classrooms. He has given tutorials at IJCAI'07 and AAAI'08. He is Editor-in-Chief of the Book Series on "Ambient Intelligence and Smart Environments" and the "Journal of Ambient Intelligence and Smart Environments". He has co-Chaired ICOST'06, AITAmI'06/07/08, and is Workshops Chair for IE'09. Ramón López-Cózar Delgado is a Professor at the Faculty of Computer Science and Telecommunications of the University of Granada, Spain.-His research interests include speech recognition and understanding, dialogue management and Ambient Intelligence. He is a member of ISCA (International Speech Communication Association), SEPLN (Spanish Society on Natural Language Processing) and AIPO (Spanish Society on HCI). Integrates engineering and computing methods that are essential for designing and implementing highly effective ambient intelligence systems Contains contributions from the world's leading experts in academia and industry Gives a complete overview of the principles, paradigms and applications of human-centric ambient intelligence systems.